Expressive Illocutionary Acts Found in The Perks of Being a Wallflower Movie - Arya Prawira Kusuma; Anak Agung Sagung Shanti Sari Dewi; I Gusti Ayu Gde Sosiowati (Pusat riset dan Inovasi Nasional, 2025)
This study aims to explore expressive illocutionary acts in the film The Perks of Being a Wallflower, focusing on the types and functions that appear in the interactions between the characters. Expressive illocutionary acts, as part of pragmatic studies, play an important role in representing emotions, attitudes, and social relationships between speakers. This study was conducted to identify in detail twelve types of expressive illocutionary acts and their four accompanying functions, thereby providing a deeper understanding of the dynamics of communication in the film. This study uses a qualitative approach with documentation and observation methods of the film's dialogue. Data analysis was carried out through three stages: data reduction, data presentation, and conclusion drawing, to obtain a systematic picture of the pattern of expressive illocutionary acts. The results show that all twelve types of expressive illocutionary acts are found in the film, with the expression